Effect of kerosene and biomass fuel as cooking medium on pulmonary function of adult nontobacco addict homemaker women residing in slums of Ahmedabad City, Gujarat - Rekha Kashyap; Ankit P Viramgami; H G Sadhu; S Raghavan; Sukh Dev Mishra; Rupal Rajesh Thasale (Wolters Kluwer Medknow Publications, 2020)
Background: Combustion of kerosene and biomass fuel in the kitchen as cooking medium is one of the major sources of indoor air pollution. Such contaminated indoor air quality adversely affects the respiratory health of exposed individuals over a period of time. Homemaker women especially residing in slum areas are always vulnerable to indoor air-pollution-related health hazards. Objectives: The objective is to assess the relationship between various socio-demographic factors and usage patterns of cooking fuel; and to determine the effect of cooking medium namely biomass, kerosene on pulmonary function parameters. Methods: A cross-sectional observational study was carried out during April 2012 - April 2016 among 531 nontobacco addicted adult primary homemaker women residing in slums of Ahmedabad city of Gujarat. Basic information-related socio-demographic parameters were collected on a pretested questionnaire. Pulmonary function test (PFT) parameters were evaluated with standard techniques. The statistical analysis was carried out with SPSS software (version 17.0). Statistical tests of significance between groups and mean along with multivariate linear regression analysis were applied. Results: Predominant cooking medium for nearly 40% of slum households were kerosene and biomass. Mean value of forced expiratory volume in the 1st s (FEV1) and FEV1/forced vital capacity (FVC) were significantly lower among Kerosene and biomass users compared to LPG users. Multivariate regression analysis with involvement of PFT parameters, cooking medium, and environmental tobacco smoke exposure (ETS) shows, deprivation of both FEV1 and FEV1/FVC were significantly related with the usage of kerosene and biomass; whereas no relation found with ETS. Conclusion: Reduction of pulmonary function parameters among the study participants were related with kerosene and biomass fuel usage in the kitchen.